Regional Competitive Analysis in Air Transport Industry in Indonesia - Rizki Andenaz, Wahyu; Anggoro, Yudo (The Indonesian Journal of Business Administration, 2017)
Abstract. Indonesia, the archipelagic country consisting of more than 17.508 islands, currently the largest one in the world, has many industries in which it should improve to. With the era of globalization and modernization, and also the free ASEAN market, in order to be able to compete with another country’s industry, Indonesia should really be able to improve its own local competitiveness first since the nation competitive advantage is grown from the local competitiveness. Air transport industry, as one of the nation’s backbone of company, could serve as one of the strategic industry to improve and to compete internationally. This means, by knowing the local region competitiveness, the national air transport industry competitiveness will improve greatly too. Using qualitative analysis method by doing interview and the quantitative analysis using Shift Share Analysis and Location Quotient, this research conducted to know some of region’s performance in the air transport industry. The result of this research could assist to a recommendation both for the government and the air transport business as a guidelines on how to improve in the future hopefully.Keywords : Air Transport, Competitive Advantage, Nation’s Competitiveness